Overqualification and Turnover Intention: The Significance of Work-Life Balance for Canadian-Born and Immigrant Employees - Ballesteros-Leiva, Felix; St-Onge, Sylvie; Arcand, Sébastien (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l’Université Laval, 2023)
SummaryThis study aims to help employers retain overqualified employees or reduce their turnover intention. Specifically, using conservation of resources (COR) theory, we tested whether employee perceptions of overqualification directly affect turnover intention and the moderating effect of work-life balance on this relationship. We study this 3-way relationship in a specific environmental context (in Canada) and compared two different groups of employees: Canadian-born and immigrant, the latter facing more challenges to integrating into the labour market and getting a job that corresponds to their qualifications. For this, there are many reasons, such as language barriers, discrimination, undervaluation of their assets, lack of work experience and lack of a professional network in the host country. We tested our hypotheses by conducting two questionnaire-based field studies in Canada: one among 227 Canadian-born employees and the other among 237 immigrant employees. Our results confirm the value of COR theory in understanding the relationship between overqualification and turnover intention among Canadian-born and immigrant employees and the moderating effect of work-life balance on this relationship among immigrants. Given the scarcity of talent, employers should do more to recognize and use their employees’ skills, whether local or immigrant. To retain their immigrant employees, employers should help them balance their work and personal lives. Finally, employers should provide overqualified immigrants with ongoing assistance (information, emotional support, tools, continuous follow-up) to help them manage their daily lives, strike a balance between their work and personal lives and, ultimately, reduce their turnover intention.AbstractUsing conservation of resources (COR) theory (Hobfoll, 1989, 2002), we first investigated the direct influence of overqualification on turnover intention. Second, we tested whether the perceived work-life balance affects the relationship between overqualification and turnover intention. To that end, we used questionnaires to conduct independent field studies of two groups of Canadian workers: 227 local human resources professionals and 237 immigrant employees. Both studies confirmed that perceived overqualification increased their intention to quit their jobs. Perceived work-life balance moderated the relationship between overqualification and turnover intention only among the immigrant employees. This paper sheds light on how perceived overqualification can affect the intention to quit a job among local and immigrant employees. It also shows how perceived work-life balance can affect the relationship between perceived overqualification and the intention to quit a job.